2007
DOI: 10.1039/b613469f
|View full text |Cite
|
Sign up to set email alerts
|

Double strand DNA cleavage with a binuclear iron complex

Abstract: Covalently linking two single strand DNA cleaving agents resulted in a new biomimetic binuclear iron complex capable of effecting oxidative double strand DNA cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…Such a sudden increase in ds cleavage activity has been observed previously, whereupon it was demonstrated that the dinuclear iron complexes were more efficient in bringing about double-strand cleavage of nicked DNA than that of supercoiled DNA. [28] In view of their structural similarity to the present complexes, this is most likely the case here as well.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Such a sudden increase in ds cleavage activity has been observed previously, whereupon it was demonstrated that the dinuclear iron complexes were more efficient in bringing about double-strand cleavage of nicked DNA than that of supercoiled DNA. [28] In view of their structural similarity to the present complexes, this is most likely the case here as well.…”
Section: Resultsmentioning
confidence: 85%
“…A correction factor of 1.31 was used to compensate for the reduced ethidium bromide uptake capacity of supercoiled DNA. [28] Figure 5. Number of double-strand cuts per DNA molecule (m) as a function of the number of single-strand cuts per DNA molecule (n) for 29 (!…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations